2021
DOI: 10.1088/2634-4386/ac1b76
|View full text |Cite
|
Sign up to set email alerts
|

A spiking central pattern generator for the control of a simulated lamprey robot running on SpiNNaker and Loihi neuromorphic boards

Abstract: Central pattern generator (CPG) models have long been used to investigate both the neural mechanisms that underlie animal locomotion, as well as for robotic research. In this work we propose a spiking central pattern generator (SCPG) neural network and its implementation on neuromorphic hardware as a means to control a simulated lamprey model. To construct our SCPG model, we employ the naturally emerging dynamical systems that arise through the use of recurrent neural populations in the neural engineering fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Progress in the physiological modeling of locomotor circuitry in the spinal cord and brainstem demonstrates the role of neural circuits in gait dynamics. However, these models typically rely on simplified (Dzeladini et al, 2014; Taga et al, 1991) biomechanical properties and cannot yet predict the deficits in gait specific to an individual (Angelidis et al, 2021; Geyer and Herr, 2010; Kuo, 2002; McCrea and Rybak, 2008). More importantly, if a hyper-realistic model of the neural and biomechanical system did exist, the relationships between the high-dimensional parameters and actual movement patterns would not likely be unique, as many parameters would not be identifiable, even given massive amounts of data, as many different parameter choices could lead to the same biomechanical output (Holmes et al, 2006; Prinz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the physiological modeling of locomotor circuitry in the spinal cord and brainstem demonstrates the role of neural circuits in gait dynamics. However, these models typically rely on simplified (Dzeladini et al, 2014; Taga et al, 1991) biomechanical properties and cannot yet predict the deficits in gait specific to an individual (Angelidis et al, 2021; Geyer and Herr, 2010; Kuo, 2002; McCrea and Rybak, 2008). More importantly, if a hyper-realistic model of the neural and biomechanical system did exist, the relationships between the high-dimensional parameters and actual movement patterns would not likely be unique, as many parameters would not be identifiable, even given massive amounts of data, as many different parameter choices could lead to the same biomechanical output (Holmes et al, 2006; Prinz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reference [ 83 ] proposed to implement a sCPG using an analog/digital VLSI device interfaced with an FPGA board, which can be directly interfaced to the actuators of a bio-mimetic robotic lamprey. Reference [ 84 ] used the sCPG model implemented in Nengo to produce the swimming gaits modulated by the high-level brainstem control of a simulated lamprey robot model in various scenarios. They showed that the robot can be controlled dynamically in direction and pace by modifying the input to the network.…”
Section: Snns In Robotic Controlmentioning
confidence: 99%
“…This was followed by chips from IBM (Merolla et al 2014, Akopyan et al 2015 and Intel (Davies et al 2018(Davies et al , 2021, which were dedicated to simulating arbitrary networks of leaky integrate-and-fire spiking neurons. These digital processors have proved to be easier to manufacture than their analog predecessors, and due to their improved availability have been used in a variety of robotic applications (Davies et al 2021, Cohen 2022 including CPGs for legged locomotion of robots ((Gutierrez-Galan et al 2019); in simulation: (Polykretis et al 2020, Angelidis et al 2021). As the second generation of these chips, which are capable of simulating up to one million simple neurons per chip, start to become available (Orchard et al 2021, Yan et al 2022, we foresee practical neural control systems running on-board legged robots approaching the scale of those in arthropod nervous systems.…”
Section: Neuromorphic Computing Hardwarementioning
confidence: 99%